PENDEKATAN MATEMATIKA REALISTIK DAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI MADRASAH IBTIDAIYAH - Uvi Karmila; Khamida Siti Nur Atiqoh (LPPM Universitas Advent Indonesia, 2021)
This study aims to improve students' mathematical communication skills by using a realistic mathematics approach. This research was conducted at one of the private MI in South Jakarta. The research method used was a quasi-experimental design in the form of a posttest only control group design. The samples of this research were students of class IV-B as the experimental class and students of class IV-C as the control class which were obtained by using purposive sampling technique on the fourth grade students with the subject of the circumference and area of ​​a flat shape. The test given is in the form of a description test with 8 items. The results of the calculation of the T-test using the Independent Sample T-Test get a significance of 0.008, meaning 0.008 <0.05, then H0 is rejected and H1 is accepted. This is also reinforced by the average value of the posttest results of the experimental class of 75.94, while the average value of the posttest results of the control class is 63.22. This shows that the mathematical communication skills of students who use the realistic mathematics approach are higher than the mathematical communication skills of students who do not use the realistic mathematics approach.